Behavior Rating Inventory of Executive Function Adult Version in Patients with Neurological and Neuropsychiatric Conditions: Symptom Levels and Relationship to Emotional Distress. (29th April 2016) - Løvstad, M.; Sigurdardottir, S.; Andersson, S.; Grane, V.A.; Moberget, T.; Stubberud, J.; Solbakk, A.K.
Abstract: Objectives: The present study explored the level of self-and informant reported executive functioning in daily living using the Behavior Rating Inventory of Executive Function-Adult Version (BRIEF-A) in a large sample comprising healthy adults and patient cohorts with neurological and neuropsychiatric disorders. The relationship to neuropsychological test performance and self-reported emotional distress was explored, as well as the applicability of U.S. normative data.Methods: Scores on the self- and informant reported BRIEF-A are presented, along with scores on standardized cognitive tests, and on rating scales of self-reported emotional distress in a Norwegian healthy comparison group ( n =115), patients with severe traumatic brain injury ( n =125), focal frontal lobe damage ( n =29), focal cerebellar lesion ( n =24), Parkinson's disease ( n =42), attention deficit hyperactivity disorder ( n =34), type II bipolar disorder ( n =21), and borderline personality disorder ( n =18).Results: Strong associations were observed between the BRIEF-A and emotional distress in both the healthy group and in neurological groups, while no or weak relationships with IQ and performance-based tests of executive function were seen. The relationship between BRIEF-A and emotional distress was weaker in the neuropsychiatric patient groups, despite high symptom load in both domains. Healthy participants tended to have BRIEF-A scores 1/2–3/4 SD below the U.S. normative mean of T score=50.Conclusions: The study demonstrates the need to interpret BRIEF-A results within a broad differential diagnostic context, where measures of psychological distress are included in addition to neuropsychological tests. Uncertainty about the appropriateness of U.S. normative data in non-U.S. countries adds to the need for interpretive caution. ( JINS, 2016, 22, 682–694)